P-326 Current real-world patterns of care for women diagnosed with uterine fibroids (UF) and heavy menstrual bleeding (HMB) in a predominantly African American (AA) population database. (30th June 2022) - Lickert, C; Dufour, R; Tilney, R; Pruett, J; Stokes, M
Abstract: Study question: What are the clinical characteristics and patterns of care in African American women diagnosed with UF and HMB compared to White women? Summary answer: The majority of the women were African American. Though similar in age, there were significant differences between the groups in multiple comorbidities and therapies. What is known already: UF (leiomyomas) are common, benign uterine tumors affecting approximately 80% of African American and 70% of White women by age 50. In the United States, marked differences exist in disease presentation, severity, treatment, outcomes, and quality of life for African American women compared with White women. African American women typically develop uterine leiomyomas at a younger age, progress to clinically significant disease at an earlier age, have larger uteri at diagnosis and are more likely to be anemic. Limited data exist on the current clinical real-world characteristics and patterns of care for African American women with UF and HMB. Study design, size, duration: This retrospective observational study identified women 18-55 years, with UF and HMB from IBM-Watson's MarketScan® Multi-state Medicaid claims database between 2010-2019. The focus was on women with diagnoses of UF (index) and HMB, appearing on the same or different claims, continuously enrolled for > 12 months pre- and post-index (censored on claim for hysterectomy). A total of ≥ 24 months of observation was available for most patients. Participants/materials, setting, methods: A total of 27, 122 women met the inclusion criteria, 16, 776 African Americans, 7, 353 Whites, and 2, 993 others or race unknown. The statistical analyses were carried out on the African American and White patients only. Descriptive analyses of baseline demographics, pre-index comorbidities and post-index treatment were performed. Chi-square tests analyses were applied to counts and t-tests analyses were applied to means. All tests used an alpha value of 0.05 for significance. Main results and the role of chance: The majority of the analytical cohort of 24, 129 women was African American (AA:69.5%; W:30.5 %). The mean (SD) follow-up time was 40.5 (24.7) months. The mean age was similar for both groups (AA:39.6 ± 7.11 years; W: 40.2 ± 7.23 years, p < 0.1). There were 48 pre-indexed comorbidities identified for analyses. The groups significantly differed on 14(29%) comorbidities. For 11 of the comorbidities, African American women were less likely to be diagnosed than White women (all Ps < 0.0001). Many of these diseases were related to bulk symptoms (e.g., pelvic pressure/pain), anxiety and depression. More African American women had diagnoses for diabetes (p = 0.0143), hypertension, and obesity (Ps < 0.0001). Though bulk symptoms were common in both groups, again fewer African American women were diagnosed than White (AA: 68.4%; W:77.0%, p < 0.0001). Post-index, African American women were more likely treated with hormone-based therapy (42.4% vs. 38.5%, p < 0.0001). Contraceptives were the most frequent form of hormonal treatment prescribed (AA:39.9%; W:35.6%). African American were on contraceptives slightly longer than White women (AA: 377.3 (522.2 days); W: 323.1 (460.2 days) (p < 0.001). Fewer African American women had a hysterectomy (AA:32.0%; W:46.8%, p < 0.001). Limitations, reasons for caution: This study was observational and descriptive in nature, which limits the ability to make conclusions regarding causality or identify women beyond the age and time constraints within the study. Additionally, claims data may be subject to reporting errors. This data is specific to Medicaid populations and may not be generalizable. Wider implications of the findings: In this Medicaid population differences in clinical characteristics and UF treatment were evident between African American and White women. The breakdown of some comorbidities did not match national prevalence by race for these conditions (e.g., depression). Further analyses are needed to determine if these differences are clinically and socially meaningful. Trial registration number: NA